Multipyrene Tandem Probes for Point Mutations Detection in DNA. (24th December 2013) - Kholodar, Svetlana A.; Novopashina, Darya S.; Meschaninova, Mariya I.; Venyaminova, Alya G.
Abstract : Here we report design, synthesis and characterization of highly sensitive, specific and stable in biological systems fluorescent probes for point mutation detection in DNA. The tandems of 3′- and 5′-mono- and bis-pyrene conjugated oligo(2′-O-methylribonucleotides), protected by 3′-"inverted" thymidine, were constructed and their potential as new instruments for genetic diagnostics was studied. Novel probes have been shown to exhibit an ability to form stable duplexes with DNA target due to the stabilizing effect of multiple pyrene units at the junction. The relationship between fluorescent properties of developed probes, the number of pyrene residues at the tandem junction, and the location of point mutation has been studied. On the basis of the data obtained, we have chosen the probes possessing the highest fluorescence intensity along with the best mismatch discrimination and deletion and insertion detection ability. Application of developed probes for detection of polymorphism C677T in MTHFR gene has been demonstrated on model systems.